Green design of cellulose nanocrystal-stabilized pickering nanoemulsions: Molecular interactions, long-term stability, and functional delivery of ginger essential oil - Olunusi, Samuel Olugbenga; Nor Hanuni, Ramli; Fatmawati, Adam; Raypah, Muna E.; Kim, Tak H.; Nurjannah, Salim; Rahmadhia, Safinta Nurindra; Juwitaningtyas, Titisari (Springer, 2026)
This work demonstrates a sustainable strategy for stabilizing and functionalizing ginger essential oil (GEO) Pickering nanoemulsions using cellulose nanocrystals (CNCs) derived from microcrystalline cellulose via a green deep eutectic solvent (DES) system. The CNCs were isolated with a high yield (95.87%) and exhibited notable crystallinity (52.74%), nanoscale morphology (< 50 nm), and thermal stability. CNC-GEO nanoemulsions were formulated at 0.3–2.0 wt% and systematically characterized for interfacial interactions, droplet stability, release kinetics, and functional properties. The 1.0 wt% CNC system achieved the most balanced performance, with a small droplet size (~ 34.7 nm), high zeta potential (–34.8 mV), low polydispersity, and > 99.7% encapsulation efficiency, as well as superior resistance to centrifugal, thermal, and freeze–thaw stress. Release studies confirmed that CNC concentration governed GEO availability: higher CNC loadings enhanced network density but slowed diffusion and reduced antioxidant efficiency. At the same time, moderate levels promoted bioactive release and stronger radical scavenging. Antibacterial assays confirmed selective inhibition, with Gram-positive S. aureus being more susceptible than Gram-negative E. coli, reflecting a distinct envelope structure. SEM and EDX analyses further revealed that CNC-GEO emulsions caused oxidative damage, membrane disruption, and elemental leakage. Collectively, these results highlight CNCs as multifunctional, food-grade stabilizers that couple structural stability with tunable bioactivity, offering a scalable route to polymer-free nanoemulsions for food preservation, nutraceutical, and pharmaceutical applications.